Deletion of Slc26a1 and Slc26a7 Delays Enamel Mineralization in Mice - Yin, Kaifeng; Guo, Jing; Lin, Wenting; Robertson, Sarah Y. T.; Soleimani, Manoocher; Paine, Michael L. (Frontiers in Physiology, 2017)
Amelogenesis features two major developmental stages—secretory and maturation. During maturation stage, hydroxyapatite deposition and matrix turnover require delicate pH regulatory mechanisms mediated by multiple ion transporters. Several members of the Slc26 gene family (Slc26a1, Slc26a3, Slc26a4, Slc26a6 and Slc26a7), which exhibit bicarbonate transport activities, have been suggested by previous studies to be involved in maturation-stage amelogenesis, especially the key process of pH regulation. However, details regarding the functional role of these genes in enamel formation are yet to be clarified, as none of the separate mutant animal lines demonstrates any discernible enamel defects. Continuing with our previous investigation of Slc26a1-/- and Slc26a7-/- animal models, we generated a double-mutant animal line with the absence of both Slc26a1 and Slc26a7. We showed in the present study that the double-mutant enamel density was significantly lower in the regions that represent late maturation-, maturation- and secretory-stage enamel development in wild-type mandibular incisors. However, the ‘maturation’ and ‘secretory’ enamel microstructures in double-mutant animals resembled those observed in wild-type secretory and/or pre-secretory stages. Elemental composition analysis revealed a lack of mineral deposition and an accumulation of carbon and chloride in double-mutant enamel. Deletion of Slc26a1 and Slc26a7 did not affect the stage-specific morphology of the enamel organ. Finally, compensatory expression of pH regulator genes and ion transporters was detected in maturation-stage enamel organs of double-mutant animals when compared to wild-type. Combined with the findings from our previous study, these data indicate the involvement of SLC26A1and SLC26A7 as key ion transporters in the pH regulatory network during enamel maturation.